2021
DOI: 10.1002/casp.2520
|View full text |Cite
|
Sign up to set email alerts
|

The mental health benefits of community helping during crisis: Coordinated helping, community identification and sense of unity during theCOVID‐19 pandemic

Abstract: Communities are vital sources of support during crisis, providing collective contexts for shared identity and solidarity that predict supportive, prosocial responses. The COVID-19 pandemic has presented a global health crisis capable of exerting a heavy toll on the mental health of community members while inducing unwelcome levels of social disconnection. Simultaneously, lockdown restrictions have forced vulnerable community members to depend upon the support of fellow residents.Fortunately, voluntary helping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
94
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 97 publications
(107 citation statements)
references
References 65 publications
(107 reference statements)
11
94
1
1
Order By: Relevance
“…This dovetails neatly with the rise in COVID‐19 mutual aid groups which was discussed in the Introduction, as it suggests that as well as strength of community identification predicting engagement in these aid groups, people's engagement with aid groups might also strengthen their community identification. Indeed, recent work conducted during the pandemic has shown that community‐based coordinated help‐giving is linked to stronger community identification and, in turn, to a stronger sense of community‐based unity (Bowe et al, 2021). People have shown a strong desire to volunteer during the pandemic (such as the million UK people who registered to volunteer with the National Health Service or with volunteer centres; Guardian, 2020), but it will be important for organizations and communities to ensure that the necessary resources are invested in order to encourage volunteer retention by helping volunteers remain engaged with and satisfied by their voluntary work (e.g., Smithson, Rowley, & Fullwood, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This dovetails neatly with the rise in COVID‐19 mutual aid groups which was discussed in the Introduction, as it suggests that as well as strength of community identification predicting engagement in these aid groups, people's engagement with aid groups might also strengthen their community identification. Indeed, recent work conducted during the pandemic has shown that community‐based coordinated help‐giving is linked to stronger community identification and, in turn, to a stronger sense of community‐based unity (Bowe et al, 2021). People have shown a strong desire to volunteer during the pandemic (such as the million UK people who registered to volunteer with the National Health Service or with volunteer centres; Guardian, 2020), but it will be important for organizations and communities to ensure that the necessary resources are invested in order to encourage volunteer retention by helping volunteers remain engaged with and satisfied by their voluntary work (e.g., Smithson, Rowley, & Fullwood, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…These observations suggest that, to a significant extent, the pandemic has been understood and addressed by people at a local community level: a conclusion that has been reinforced further by the rise of COVID‐19 mutual aid groups (Bowe et al, 2021; Tiratelli & Kaye, 2020; Wakefield, Bowe, & Kellezi, 2021). These groups involve volunteers working together to support the most vulnerable in their community (e.g., the elderly, those with chronic illness, and others who were advised to shield themselves fully from the virus) by delivering food and medicine, sharing information and providing practical and emotional support (Mao, Fernandes‐Jesus, Ntontis, & Drury, 2020).…”
Section: Introductionmentioning
confidence: 96%
“…There are reasons to propose that perceived global common fate and shared threat will increase identification with others who share the same fate, and through this with help extended to those others, also in the context of the COVID‐19 crisis. As demonstrated in the context of many disasters, suffering from the same adversity can create new shared identities and solidarity with others who would formerly have been seen as outgroup members (Bowe et al, 2021 ; Ntontis et al 2021 ; Solnit, 2010 ). For example, in the context of a flooded community, common fate was positively associated with an emerging sense of community and identification with the group, as well as with social support (Ntontis et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, increasing social ties is often a benefit not only for long-term volunteers, but also for short-term and/or occasional volunteers (Hyde et al, 2014). Similar outcomes have been found in the COVID-19 context, with a recent study showing that community helping predicts community identification and unity during the pandemic, which in turn seems to increase well-being (Bowe et al, 2021).…”
Section: Understanding Sustained Participation In Covid-19 Mutual Aid Groupsmentioning
confidence: 57%
“…Most of the published research on COVID-19 mutual aid groups has been descriptive (see Mao et al, 2021 for a review). However, some recent work has started to examine psychological processes (Bowe et al, 2021;Wakefield et al, 2021;Mao et al, in press), which is useful for addressing our questions of how such groups can be sustained.…”
Section: Community Solidarity In the Covid-19 Pandemicmentioning
confidence: 99%